Analyzing ‘Working from Home’ as ‘the New Normal’ for Working Women from Feminist’ Lens - Savitri, Dewayani; Sigiro, Atnike Nova (Jurnal Perempuan, 2021)
Working from home, when workers accomplish their duties and works at home, have become an important phenomenon during the Covid-19 pandemic, that have been practiced for more than a year since the Covid-19 outbreak. For working women, working from home have combined two women’s duties in one place at the same time, those are their responsibilities as workers, and their responsibilities at homes – including care work, as the common gender role of women. This article aims to explore whether working from home could become a conducive mode of work for women and family’s welfare. What factors do the policy makers need to consider, so that working from home would not reproduce gender inequality against women. This article was developed from literature studies on the analysis and policy framework at the global level, and also several existing researches about the challenges that have been faced by working women during the Covid-19 pandemic in Indonesia.